Representasi Maskulinitas Dalam Iklan Televisi Pond’s Men #Lelakimasakini (Analisis Semiotika Roland Barthes Terhadap Representasi Maskulinitas) - Friska Dewi Yuliyanti; Atwar Bajari; Slamet Mulyana (Jurnal Komunikasi, 2017)
This research aims to know the meaning of denotation, the connotation and the myth or ideology in television commercials POND'S Men that represent the masculine with #LelakiMasaKini edition. The method used in this research is the Semiotic analysis methods. The Semiotic analysis used in this research is the Semiotic Roland Barthes. The results of this research show that there are; meaning denote, the connotation and the myth or ideology in television commercials POND'S #LelakiMasaKini. The results obtained from the signs of the dominant in the preview scenes that are taken in accordance with the criteria that have been determined. Advertising on Rio Dewanto version described three meaning denotes, three meaning of the connotations and three myths. On the version of the advertisement, Keenan Pearce described three meaning denotes, three the meaning of the connotations and three myths or ideologies and on the version of the Marshall Sastra described three meaning denotes, three the meaning of the connotations and 3 myths or ideologies. Concluded the side or the form of masculinity is promoted of the physical appearance of the type of men who tend to metrosexual, the dream of women, the leader success, lack men who think creatively and have hobbies.Penelitian ini bertujuan untuk mengetahui makna denotasi, konotasi serta mitos atau ideologi dalam iklan televisi POND’S Men yang merepresentasikan maskulinitas dengan edisi #LelakiMasaKini. Metode yang digunakan dalam penelitian ini adalah metode analisis semiotik. Analisis Semiotik yang digunakan dalam penelitian ini adalah analisis semiotik Roland Barthes. Hasil dari penelitian ini menunjukkan bahwa terdapat makna denotasi, konotasi serta mitos atau ideologi pada iklan televisi POND’S Men #LelakiMasaKini. Hasil itu diperoleh dari tanda-tanda dominan pada cuplikan adegan-adegan yang diambil sesuai dengan kriteria yang telah ditentukan. Pada iklan versi Rio Dewanto digambarkan 3 makna denotasi, 3 makna konotasi, dan 3 mitos. Pada iklan versi Keenan Pearce digambarkan 3 makna denotasi, 3 makna konotasi dan 3 mitos atau ideologi dan pada versi Marshall Sastra digambarkan 3 makna denotasi, 3 makna konotasi dan 3 mitos atau ideologi. Disimpulkan sisi atau bentuk maskulinitas yang dipromosikan adalah tampilan fisik tipe laki-laki yang cenderung metroseksual, dambaan wanita, pemimpin yang cerdas dengan kesuksesan, lak-laki yang berpikir kreatif dan memiliki hobi.